The Effects of Applying Revenue Management on Customer Satisfaction in Airline Industry: An Experimental Study in Indonesia - Lupiyoadi, Rambat; Putra, Bramana (ASEAN Marketing Journal, 2021)
This research mainly discusses about the effects of applying revenue management, specifically in the contexts of inventory control (variation in ticket prices for the same flight and class) and denied boarding (permissibility of reservations exceeding carrying capacity as a hedging practice over the possibility of tickets cancellation) on the customers’ satisfaction toward airlines in Indonesia. Experimental method was applied on the research, involving students from University of Indonesia asparticipants. The results showed that inventory control policy partly affected customer satisfaction, while the denied boarding policy fully affected their satisfaction. These research findings can contributeto further studies on consumers’ behaviour in dynamic airlines industry, mainly in emerging markets such as Indonesia